Clinical spectrum and short-term outcomes of multisystem inflammatory syndrome in children in a south Indian hospital - Muruganantham Balagurunathan; Thrilok Natarajan; Jothilakshmi Karthikeyan; Venkateshwaran Palanisamy (The Korean Pediatric Society, 2021)
Background Multisystem inflammatory syndrome in children (MIS-C) is a new hyperinflammatory variant that evolved during the coronavirus disease 2019 pandemic. Although the precise pathophysiology of MIS-C is uncertain, it is thought to be due to immune dysregulation occurring after recovery from acute infection. Purpose Our study aimed to analyze the clinical spectrum, laboratory parameters, imaging characteristics, treatment strategies, and short-term outcomes of children with a diagnosis of MIS-C. Methods This retrospective and prospective observational study included children less than 16 years of age who were admitted to the pediatric unit of a tertiary care teaching hospital in south India between August 2020 to January 2021 with a diagnosis of MIS-C according to World Health Organization criteria. Results Twenty-one children were included in the analysis; all had fever with variable combinations of other symptoms. The mean age was 6.9 years; 71.4% were male. Gastrointestinal (80.9%) and cardiovascular (80.9%) systems were the most commonly affected. The majority of children had elevated inflammatory markers, and 16 (76.2%) had echocardiographic abnormalities mimicking Kawasaki disease. Eleven children (52.4%) required intensive care admission, 3 (14.3%) required supplemental oxygen, and 4 (19%) required inotropes. Nine (42.9%) were treated with intravenous immunoglobulin alone, 6 (28.6%) with steroids alone, and 3 (14.3%) with steroids and immunoglobulin. The median hospital stay was 6 days; there were no fatalities. Overweight/obesity, elevated ferritin, and mucocutaneous involvement were significantly associated with a prolonged hospital stay (≥7 days). Sixteen children (76.2%) were followed up till now and all of them had no clinical concerns. Conclusion MIS-C is an emerging disease with variable presentation. A high index of suspicion is necessary for its early identification and appropriate management. Further research is essential for developing optimal treatment strategies.